The Tax lawsuit In the UAE Tax Procedures Law No (28) of 2022 - Mouna Mahmoud Edlbi (Journal of Legal Sciences, 2024)
Taxes are one of the most important revenues of the state, which it uses to cover public expenditures in order to meet public needs and promote the development process, and this makes us in front of the state’s right to these taxes and the need to preserve them, and the taxpayer’s right to pay the tax due only in accordance with the provisions stipulated by law. Many taxes disputes arise as a result of the application of tax legislation, and the matter is related to the clarity and transparency of the legal rules, the more certainty is available in those legislations mean less size of these disputes of course, to solve these disputes is usually assigned to the tax administration at the first, and then to the committees formed for this purpose, and it is also possible to go to the judicial side to resolve these disputes when administrative settlements fail, and considering that this topic is very important, especially In the UAE, because it applied taxes later ,in the Tax Procedures Law which applied in 2017 and modified in 2022, has some reservations in this regard, especially on the scope of the conditions for filing this lawsuit, so in this research we will review the parties to this lawsuit and its conditions and the competent judiciary to consider it in the UAE , and we will focus the points that need to be reconsidered in order to suit the aspirations of the UAE in development in all aspects